SISTEM INFORMASI JASA SOL DAN PENJUALAN SEPATU SECARA ONLINE - Alfina Musfiroh; Nur Hasanah; Nulngafan (CV Nature Creative Innovation, 2024)
A shoe sole business is a business that provides shoe repair services such as damaged or loose shoe soles. Even though there are many online buying and selling sctivities using various marketplace platforms, the information system for sole and shoe sales services in Sindupaten Village does not yet use an online system. This makes it difficult for customers to get information on the correct place or location for shoe sole service and buying and selling activities need to use digital methods so that they can be accessed online. Based on these problems, an Online Shoe and Sole Services Information System was created.with data collection methods using observation, interview, and documentation techniques. The system development method uses the waterfall method. This system can make it easier for customers to search for information on sole service and buy shoe products because it is done online and makes it easier for sellers to carry out buying anda selling activities online.